“EFFICIENCY ANALYSIS OF 3 DIFFERENT FUEL TOWARDS GASOLINE FUEL MOTORS ON EME 35 ENGINES IN LAPAN SURVELLANCE UAV-02 (LSU-02)” - Ramadhan, M. Fajar; Bismantolo, Putra; Suryadi, Dedi; Utama, Agus Bayu (UNIB Press, 2024)
This study aims to analyze the efficiency of three different types of fuel on the EME 35 engine on the LSU 02 aircraft. The fuel used is Pertalite, Pertamax, and Pertamax turbo. The method used in this study was an experiment using the LSU 02 aircraft as the research object. The data is taken from measurements of fuel consumption and engine performance on each type of fuel. The analysis is carried out by comparing the efficiency and performance of the engine on each type of fuel used. The results showed that the efficiency and performance of the engine on Pertamax fuel was better than that of Pertamax turbo and Pertalite. Fuel consumption on Pertamax is more efficient than Pertalite and Pertamax turbo, so that Pertamax is more efficient in fuel use. In addition, engines on Pertamax fuel have better performance with greater power and are more stable compared to Pertalite and Pertamax turbo. Therefore, it is recommended to use Pertamax fuel in the EME 35 engine on the LSU 02 aircraft to achieve better efficiency and performance.